2012
DOI: 10.1186/2192-2853-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel red fluorophores with superior performance in STED microscopy

Abstract: In optical microscopy, most red-emitting dyes provide only moderate performance due to unspecific binding, poor labeling efficiency, and insufficient brightness. Here we report on four novel red fluororescent dyes, including the first phosphorylated dye, created by combining a rigidized rhodamine backbone with various polar groups. They exhibit large fluorescence quantum yields and improved NHS ester stability. While these fluorophores are highly suitable for fluorescence microscopy in general, they excel in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 15 publications
1
84
0
Order By: Relevance
“…The measured diameter relative to the size of the whole nuclear pore complex confirmed that the antibody was indeed bound to Nups in the center of the NPC 29 . The resolution of 19 nm is one of the new record of STED super-resolution in biological applications 3236 . The resolution improvement is largely because two-fold resolution enhancement can be obtained without increasing the depletion laser power.…”
Section: Resultsmentioning
confidence: 99%
“…The measured diameter relative to the size of the whole nuclear pore complex confirmed that the antibody was indeed bound to Nups in the center of the NPC 29 . The resolution of 19 nm is one of the new record of STED super-resolution in biological applications 3236 . The resolution improvement is largely because two-fold resolution enhancement can be obtained without increasing the depletion laser power.…”
Section: Resultsmentioning
confidence: 99%
“…(d) Higher-order photobleaching from the first excited electronic state S 1 , as exemplified for the organic dyes pDI and pTDI and for eGFP. Absorption spectra of S 0 (blue) and S 1 (red) and fluorescence development of new bright and photostable dyes, often specialized for STED applications, has and continuously will enhance the applicability and flexibility of experiments using this superresolution technique Kolmakov et al 2010aKolmakov et al , 2010bKolmakov et al , 2012Mitronova et al 2010;Wurm et al 2012).…”
Section: Photo-physical and -Chemical Considerations In Sted Nanoscopymentioning
confidence: 99%
“…The only requirement is the proper adjustment of imaging conditions to their photophysical properties. Live cell imaging with fl uorescent proteins has been demonstrated (Morozova et al 2010 ), and posttranslational labeling with fl uorescence dyes emitting in the red and near-IR and more suitable for STED appears to be a promising alternative (Lukinavičius et al 2013 ;Wurm et al 2012 ).…”
Section: Stimulated Emission Depletion (Sted) Microscopymentioning
confidence: 99%